Complete sequences of IncHI1 plasmids carrying blaCTX-M-1 and qnrS1 in equine Escherichia coli provide new insights into plasmid evolution - Dolejska, Monika; Villa, Laura; Minoia, Marco; Guardabassi, Luca; Carattoli, Alessandra (The Journal of antimicrobial chemotherapy, 2014)
OBJECTIVES: To determine the structure of two multidrug-resistant IncHI1 plasmids carrying blaCTX-M-1 in Escherichia coli isolates disseminated in an equine clinic in the Czech Republic. METHODS: A complete nucleotide sequencing of 239 kb IncHI1 (pEQ1) and 287 kb IncHI1/X1 (pEQ2) plasmids was performed using the 454-Genome Sequencer FLX system. The sequences were compared using bioinformatic tools with other sequenced IncHI1 plasmids. RESULTS: A comparative analysis of pEQ1 and pEQ2 identified high nucleotide identity with the IncHI1 type 2 plasmids. A novel 24 kb module containing an operon involved in short-chain fructooligosaccharide uptake and metabolism was found in the pEQ backbones. The role of the pEQ plasmids in the metabolism of short-chain fructooligosaccharides was demonstrated by studying the growth of E. coli cells in the presence of these sugars. The module containing the blaCTX-M-1 gene was formed by a truncated macrolide resistance cluster and flanked by IS26 as previously observed in IncI1 and IncN plasmids. The IncHI1 plasmid changed size and gained the quinolone resistance gene qnrS1 as a result of IS26-mediated fusion with an IncX1 plasmid. CONCLUSIONS: Our data highlight the structure and evolution of IncHI1 from equine E. coli. A plasmid-mediated sugar metabolic element could play a key role in strain fitness, contributing to the successful dissemination and maintenance of these plasmids in the intestinal microflora of horses.
Keywords: Plasmids; horses; fructooligosaccharides; IncX1; infekce vyvolané Escherichia coli; Česká republika; Sequence Analysis, DNA; beta-Lactamases; sekvenční analýza DNA; molekulární sekvence - údaje; Escherichia coli Infections; molekulární evoluce; Evolution, Molecular; Escherichia coli; beta-laktamasy; Gene Order; Czech Republic; Synteny; proteiny z Escherichia coli; Animals; Escherichia coli Proteins; zvířata; metabolické sítě a dráhy; plazmidy; IncHI1; koně; Molecular Sequence Data; CTX-M-1; syntenie; Metabolic Networks and Pathways; Horses; pořadí genů